Two Visual Training Paradigms Associated with Enhanced Critical Flicker Fusion Threshold - Zhou, Tianyou; Náñez, Jose E.; Zimmerman, Daniel; Holloway, Steven R.; Seitz, Aaron (Frontiers in Psychology, 2016)
Critical flicker fusion thresholds (CFFT) describe when quick amplitude modulations of a light source become undetectable as the frequency of the modulation increases and are thought to underlie a number of visual processing skills, including reading. Here, we compare the impact of two vision training approaches (ULTIMEYES and directional dot motion) compared to an active control group trained on Sudoku. The three training paradigms were compared on their effectiveness for altering Critical Flicker Fusion Threshold (CFFT). Directional dot motion and ULTIMEYES training resulted in significant improvement in CFFT, while the Sudoku group did not yield significant improvement. This finding indicates that the two motion-related conditions (dot motion and ULTIMEYES) are effective methods for studying the role of low-level visual motion training on plasticity of higher order perceptual tasks, e.g. CFFT. The results and implications for potential future vision-based brain plasticity research involving high-order cognitive processes such as reading ability are discussed.